2001
DOI: 10.1093/bja/86.5.683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of haemoglobin-based oxygen carrier Hemoglobin glutamer-200 (bovine) on intestinal perfusion and oxygenation in a canine hypovolaemia model

Abstract: The objective of this investigation was to study the effects of the first marketed haemoglobin-based oxygen carrier, Hemoglobin glutamer-200 (bovine) (Hb-200) (Oxyglobin) on splanchnic perfusion and oxygenation in a canine model of acute hypovolaemia. Twelve anaesthetized dogs [mean weight 30.8 (S.D. 1.4) kg] were instrumented for recordings of heart rate (HR), mean arterial pressure (MAP), central venous pressure (CVP), cardiac output and cranial mesenteric arterial (CMA) and venous blood flows (CMV). Total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 30 publications
(17 reference statements)
7
54
0
Order By: Relevance
“…It shares most properties with Hb glutamer-250 (bovine; Hemopure [formerly HBOC-201], Biopure) (7), which is currently in phase III clinical trials and approved for use in humans in South Africa. Previous studies with low doses of Hb-200 (8,9) and HBOC-201 (10) revealed an improvement of hemodynamic functions, yet a significantly smaller increase in arterial oxygen content and oxygen delivery after HBOC infusion than expected based on the amount of Hb administered. Therefore, in the present study, our primary goal was to analyze whether infusion of Hb-200 will dosedependently and to a greater extent than conventional plasma expanders increase systemic oxygen delivery and tissue oxygenation in dogs subject to isovolemic resuscitation after acute blood loss.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…It shares most properties with Hb glutamer-250 (bovine; Hemopure [formerly HBOC-201], Biopure) (7), which is currently in phase III clinical trials and approved for use in humans in South Africa. Previous studies with low doses of Hb-200 (8,9) and HBOC-201 (10) revealed an improvement of hemodynamic functions, yet a significantly smaller increase in arterial oxygen content and oxygen delivery after HBOC infusion than expected based on the amount of Hb administered. Therefore, in the present study, our primary goal was to analyze whether infusion of Hb-200 will dosedependently and to a greater extent than conventional plasma expanders increase systemic oxygen delivery and tissue oxygenation in dogs subject to isovolemic resuscitation after acute blood loss.…”
mentioning
confidence: 82%
“…Methods were essentially as described and discussed in detail previously (8,9) with modifications mentioned below.…”
Section: Methodsmentioning
confidence: 99%
“…However, systemic vasoconstriction is not paralleled by a reduced regional organ blood flow or impaired microcirculation [22,23]. In contrast, animal studies have shown improved tissue oxygenation during blood exchange, restoration of the pancreatic microcirculation and tissue oxygen tensions, and reduced acidosis with better mucosal integrity of the intestine after resuscitation from hemorrhagic shock with different HBOC [16,24,25]. In experimental acute pancreatitis bovine HBOC-301 was able to significantly reduce histologic tissue damage in rats [26].…”
Section: Animal Experiments With Hemoglobin-based Oxygen Carriersmentioning
confidence: 99%
“…Hemoglobin-glutamer (HbG) 200 (Oxyglobin; Biopure, Cambridge, MA) is a hemoglobin-based oxygen carrying (HBOC) solution capable of improving organ oxygenation by increasing plasma and total hemoglobin concentration and an increased oxygen unloading in the microcirculation, due to its low oxygen affinity [17]. It contains 13 g/dL polymerized hemoglobin of bovine origin in a modified lactated Ringer's solution, which circulates in plasma and immediately transports oxygen to tissues upon infusion.…”
Section: Introductionmentioning
confidence: 99%
“…The osmolality of the solution is 300 mOsm/kg. The terminal elimination half-life of the drug is estimated to range between 18 and 43 h for dosages of 10 to 13 mL/kg [17].…”
Section: Introductionmentioning
confidence: 99%